The neuromechanical adaptations to Achilles tendinosis - Yu‐Jen Chang; Kornelia Kulig (2015)
Achilles tendinosis is a localized degenerative musculoskeletal disorder that develops over a long period of time and leads to a compliant human Achilles tendon. We demonstrate that the compliant Achilles tendon elicited a series of adaptations from different levels of the human movement control system, such as the muscle-tendon interaction, CNS control and other muscles in the lower leg. These results illustrate the human body's capacity to adapt to tendon pathology and provide the physiological basis for intervention or prevention strategies. Human movement is initiated, controlled and executed in a hierarchical system including the nervous system, muscle and tendon. If a component in the loop loses its integrity, the entire system has to adapt to that deficiency. Achilles tendon, when degenerated, exhibits lower stiffness. This local mechanical deficit may be compensated for by an alteration of motor commands from the CNS. These modulations in motor commands from the CNS may lead to altered activation of the agonist, synergist and antagonist muscles. The present study aimed to investigate the effect of tendon degeneration on its mechanical properties, the neuromechanical behaviour of the surrounding musculature and the existence of the CNS modulation accompanying tendinosis. We hypothesize that the degenerated tendon will lead to diminished tissue mechanical properties and protective muscle activation patterns, as well as an up-regulated descending drive from the CNS. Strong evidence, as reported in the present study, indicates that tendinotic tendons are more compliant compared to healthy tendons. This unilateral involvement affected the neuromuscular control on the involved side but not the non-involved side. The muscle-tendon unit on the tendinotic side exhibits a lowered temporal efficiency, which leads to altered CNS control. The altered CNS control is then expressed as an adapted muscle activation pattern in the lower leg. Taken together, the findings of the present study illustrate the co-ordinated multi-level adaptations to a mechanical lesion in a tendon caused by pathology.